The Impact of Generation Z’s Greenwashing Perception on Green Purchase Intention in the Context of Indonesian H&M Consumers - Luh Prascitta Putri Ariawan; Alldila Nadhira Ayu Setyaning (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This research project studies at the impact of greenwashing perception on green purchasing intention among Generation Z customers in Indonesia, specifically at the fast fashion brand H&M. Based on Perceived Risk Theory and adapted from Lu et al. (2022), the study incorporates financial perceived risk and green perceived risk as mediating variables, as well as the moderating influence of impulsive purchasing behavior. The study used a quantitative approach, collecting responses from 287 individuals via an online survey and analysing the data with Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings show that greenwashing perceptions considerably raise financial and environmental risk. Furthermore, the idea of greenwashing harms green purchase intention, as does the perceived financial risk. However, green perceived risk has no significant impact on green purchasing intention, and impulsive buying has no significant moderating effect on the association between greenwashing perception and financial risk. These findings indicate that Generation Z customers in Indonesia are susceptible to greenwashing and that financial reasons weigh more heavily in purchasing decisions than environmental concerns. The findings have important implications for sustainable marketing tactics in the fast fashion industry.